A Computational DFT Insight into the Optimized Structure, Electronic Structures, Spectroscopic Analysis, and Thermodynamic Parameters of the Cytosine Molecule - Basnet, Khakendra; Neupane, Bhijan; Gharti Magar, Pima; Uprety, Roshika; Rai, Krishna Bahadur (Amrit Research Journal, 2024)
The optimized structure of the Cytosine molecule was achieved in 12 steps, yielding an optimization energy of -10749.84 eV. The HOMO-LUMO energy gap of 4.94 eV indicates chemical stability. The oxygen atom exhibits the most negative potential and the hydrogen atom shows the most positive potential. The density of states reveals an energy gap of 4.92 eV, confirming equivalent orbital energy levels. Calculated hardness (2.47 eV) and softness (0.41 eV-1) suggest stability and polarizability. The chemical potential is -3.97 eV, and the electronegativity is 3.97 eV. The electrophilicity index of 3.19 eV indicates a strong electrophilic behavior. Mulliken charge analysis identifies H13 with the highest positive charge and N5 with the highest negative charge. Vibrational analysis shows C-H vibrations at 3100-3300 cm-1, N-H at 3500-3700 cm-1, and C=O at 1771.10 cm-1. Thermodynamic properties such as heat capacity, internal energy, enthalpy, and entropy increase with temperature, while Gibbs free energy decreases.